2019
DOI: 10.5897/ajar2019.13919
|View full text |Cite
|
Sign up to set email alerts
|

Wheat response to water stress condition at different growth stages in Amibara, Ethiopia

Abstract: To evaluate the effect of water stress at different crop growth stages on yield, yield components and water use efficiency, a field experiment was carried out in 2015/2016, 2016/2017 and 2017/2018 for bread wheat (Gambo variety) at Werer Agricultural Research Center. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications having 15 experimental treatments. Combination of water stress with crop growth stages was applied in the major investigation of the experiment. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…On the other hand, the lowest WP (1.1 kg m −3 ) was obtained at 100% ETc and this was statistically similar with 85% ETc. In a wheat response to a stage-wise DI study from southeastern Ethiopia, Hassen et al (2019) found the highest grain yield (3 t ha −1 ) at full irrigation, which was similar to yields of other DI strategies that irrigated at all stages except the initial stage (2.9 t ha −1 ), and irrigation of all stages except maturity (2.8 t ha −1 ) stages. This means that DI application at less water stress-sensitive growth stages could be an option to increase overall yield and WP with the same amount of water with a very small yield reduction.…”
Section: Wheatsupporting
confidence: 61%
“…On the other hand, the lowest WP (1.1 kg m −3 ) was obtained at 100% ETc and this was statistically similar with 85% ETc. In a wheat response to a stage-wise DI study from southeastern Ethiopia, Hassen et al (2019) found the highest grain yield (3 t ha −1 ) at full irrigation, which was similar to yields of other DI strategies that irrigated at all stages except the initial stage (2.9 t ha −1 ), and irrigation of all stages except maturity (2.8 t ha −1 ) stages. This means that DI application at less water stress-sensitive growth stages could be an option to increase overall yield and WP with the same amount of water with a very small yield reduction.…”
Section: Wheatsupporting
confidence: 61%
“…Decline in water reserves conflict for maintenance of food requirements of the world population. Water supply is going to decline progressively but nutrients requirements increasing due to increase in population [9,10].…”
Section: Introductionmentioning
confidence: 99%